Pemanfaatan Aplikasi Google Form berbasis Online sebagai Alat Tes Tertulis Belajar Fisika pada Masa Pandemi Covid-19 - Abdin, Abdin; Saefuddin, Asrun; Kasman, Kasman (Universitas Halu Oleo, 2021)
This study aims to provide new innovations to physics education lecturers in the use of the online-based google form application as a written test tool for learning physics during the Covid-19 pandemic in solving problems in other fields. In addition, it motivates physics education lecturers to use online technology in the implementation of lectures in the room. The target of this research is the product of using online-based forms as a written test for learning physics during the Covid-19 pandemic. The resulting products are expected to: (a) improve students 'physics learning abilities, (b) help students to be more independent and attract students' attention in taking basic physics courses, (c) motivate physics education lecturers to use online technology in the implementation of lectures in the room. The research method is development research or research and development using a development model which consists of five stages, namely: (1) initial investigation (initial), (2) design (design), (3) realization / construction (realization / construction), (4) testing, evaluation, and revision (test, evaluation, and revision), (5) implementation (implementation). The results of this study are the feasibility of using the Google-based online form as a written test for learning physics during the Covid-19 pandemic. It can be seen based on the results or validity of material experts obtained by an average score of 92.5 in the valid category For service or validity from media experts, the mean is 93.85 with the valid category. The effectiveness of using the online-based google form application as a written test through the ability of students to get an average pretest score of 57.50 and a postest score of 80.63 an increase in increase. This is also seen from the t test paired with the value of t table = 2.04 <tcount = 9.26, so H0 is rejected, which means a significant increase in the ability of students.